Does Corporate Social Responsibility (CSR) Interact with Sustainable Development Goals (SDG)? A Literature Review of The Contribution and Implications of CSR To The SDGS - Cristian Armando RIOS-LAMA; Jorge Alberto VARGAS-MERINO (Communications of International Proceedings, 2022)
Careless and uncontrolled human growth has caused great discomfort in the global ecosystem, as well as social challenges inherent to human relations; in response to this situation, sustainable development was born, encompassing social, environmental and economic problems. In this concept, companies play a fundamental role in the search for sustainable development, since they develop corporate social responsibility activities. Therefore, this research seeks to analyze theoretical and empirical studies of the contributions or implications of corporate social responsibility to sustainable development in the last 6 years, being a systematic literature review, where the application of search strategies and criteria of scientific rigor give a systematization of 54 articles, 92% belonging to Q1. In conclusion, both concepts complement each other, being corporate social responsibility vital for sustainable development, although the motivations to carry out such activities do not seek this purpose.
Keywords: Corporate Social Responsibility; Sustainable Development; SDGS; Sustainability